Genomic Analysis of Four Human Metapneumovirus Prototypes - Piyaratna, Rohith (2011)
Human metapneumovirus (HMPV) is an important cause of acute respiratory illness in children. We determined the complete genome sequence of four strains of HMPV representing each of the four lineages. These sequences were compared with published HMPV genome sequences. Most genes were conserved between the genetic lineages (79.5%-99.6%), though nucleotide diversity was greater than amino acid diversity, suggesting functional constraints on mutation. However, the SH and G open reading frames were more variable (mean 76.4% and 59.0% aa identity, respectively), with mostly nonsynonymous changes, suggesting selective pressure on the SH and G proteins. Gene-start regions were largely conserved between genes and viruses, while gene-end sequences were conserved between viruses but not between genes. The SH-G and G-L intergenic regions were extremely long (~200 nt) and have no defined function, yet were highly conserved within major groups. These findings highlight broadly conserved regions of the HMPV genome and suggest unidentified biological roles for SH and G.